2018
DOI: 10.1017/s1355617718000115
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytic Review of Memory Impairment in Behavioral Variant Frontotemporal Dementia

Abstract: This study points to memory disorders in patients with bvFTD, with performance at an intermediate level between controls and patients with AD. This indicates that, instead of being an exclusion criterion for bvFTD diagnosis, memory deficits should be regarded as a potential integral part of the clinical spectrum. (JINS, 2018, 24, 593-605).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 90 publications
2
16
0
Order By: Relevance
“…The FCSRT is commonly used by neuropsychologists as it involved both free and cued-based recalls, thus allowing us to tackle the commonest criticize made to studies only addressing free recall. In addition, the poor discrimination power of memory testing in the context of the differential diagnosis between AD and FTLD, although it was never the focus of a neuropathological study before, has been shown independently of the test used and the memory component explored (Bertoux et al 2018;Poos et al, 2018). In consequence, we believe that it is likely that our findings could be generalizable with other common verbal memory assessment.…”
Section: Discussionmentioning
confidence: 67%
“…The FCSRT is commonly used by neuropsychologists as it involved both free and cued-based recalls, thus allowing us to tackle the commonest criticize made to studies only addressing free recall. In addition, the poor discrimination power of memory testing in the context of the differential diagnosis between AD and FTLD, although it was never the focus of a neuropathological study before, has been shown independently of the test used and the memory component explored (Bertoux et al 2018;Poos et al, 2018). In consequence, we believe that it is likely that our findings could be generalizable with other common verbal memory assessment.…”
Section: Discussionmentioning
confidence: 67%
“…Consensual diagnostic criteria for bvFTD state that episodic memory is relatively spared in bvFTD [2]. However, there is increasing evidence that episodic memory impairment occurs in bvFTD [37, 38] in a similar degree as observed in Alzheimer’s disease [19, 27, 3941]. Actually, amnesia in bvFTD is associated with the involvement of medial temporal structures, such as hippocampal and perihippocampal regions [37, 3941].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical profile of FTD is typically characterized by behavioural and language disturbances, with cognitive deficits in executive function and relative sparing of memory and visuospatial abilities [ 1 , 2 ], whereas the first symptoms of AD are usually episodic memory and visuospatial impairments [ 3 ]. Differential diagnosis in a young-onset population is complicated by frequent atypical presentations and clinical overlap between the two entities, with significant memory deficits in FTD [ 4 ], and predominant ‘frontal’ (dysexecutive and behavioural) and language variants of AD being described [ 5 ], often leading to misdiagnosis and/or diagnostic delay. Early diagnosis is, however, essential for proper patient and caregiver management and planning, non-pharmacological symptomatic treatment, and patient stratification in upcoming clinical trials [ 6 ].…”
Section: Introductionmentioning
confidence: 99%